Kesetaraan Gender dalam Hukum Kewarisan Islam Perspektif M. Syahrur - Fatimatuz zahro; Shinta Pramesti K.M (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Islam beautifully respects and glorifies the dignity of a woman. This is proven in the Qur'an Surah a Nisa' verse 11 that women are also entitled to a share in the inheritance. The actual phenomenon is that currently, women are considered capable of being independent. At the same time, the concept of inheritance distribution is guided by justice and is not measured by the level of equality. The problem of gender equality in the distribution of portions of inherited assets is like a snowball that rolls further and further and raises issues of gender equality that have occurred to date. The gender gap in inheritance law appears against the background of some parties whose sense of justice is not fulfilled. The portion of the distribution often triggers disputes between men and women. This research focuses on applying the inheritance distribution system according to classical Fiqh Mawaris with Islamic inheritance in KHI and analyzes the problems of gender equality in Islamic legal inheritance. This study uses a type of normative legal research. This method focuses on legal principles and finds coherent truths. Legal rules are conceptualized as norms in a broad scope. Sources from the normative side come from laws and regulations, court decisions, and doctrines from legal scientists with the approach taken. The concept in this research is carried out by looking at various points of view and phenomena of doctrinal development in the science of law. This study concludes that from the portion of the heirs, there are similarities between classical rose is and KHI. Still, the difference is read in the distribution of inheritance in classical Islamic law. The compilation of Islamic law is the way to draw lineages based on males as a result of female offspring which is called dzawil arham is covered by men. In contrast, in the compilation of Islamic law, the way to draw lineages is based on a bilateral principle so that female offspring are not covered by men, Islamic inheritance law in Indonesia seeks to reform to accommodate a sense of justice. However, its efforts it does not necessarily reduce the problems of gender equality that exist in society.